GAMBARAN KECENDERUNGAN KECANDUAN PORNOGRAFI PADA ANAK SEKOLAH DASAR DI JAKARTA BARAT - Safitri, Safitri; Respati, Winanti Siwi; Luthfi, Aziz (Jurnal Psikologi : Media Ilmiah Psikologi, 2017)
AbstractPornography has become a lot of consumption of children, because the porn industry has been targeting children who have not baligh as a target. Therefore, early detection is needed to recognize the propensity of pornography addiction to children through fun and useful activities. The purpose of this research is to see the picture of pornography addiction tendency in elementary school children. The quasi-experimental research method, which will measure the propensity of pornography addiction through psychodrama activities and puberty training, with a modified gauge of Kimberly Young's Internet addiction gauge, with a realibility of 0.72. Respondents come from 3 Primary Schools in West Jakarta as many as 190 Students. Puberty preparation training activities that begin with psychodrama are well done for the detection of pornography addiction. The majority of students have seen pictures / scenes of pornography (86.3%), 73.2% accidentally, viewed at home 30.5%. And internet cafe 22.1%, via Hp and comics 39.5%% and games 37 , 4%. Feelings after seeing pornography majority disgust (46.4%), mediocre 15.8%, aroused 2.6%. Attitude after seeing the majority of pornography kapok (62.6%), the average 15.8%, and addicted 2.6%. Rates of pornography addiction tend to be moderate (69.5%) low 18.9% and high 11.6%. There is a relationship between student activity and pornography addiction rate with the origin of the school. Keywords: pornography, psychodrama, puberty training AbstrakPornografi sudah banyak menjadi konsumsi anak-anak, karena industri pornografi sudah menyasar anak-anak yang belum baligh sebagai targetnya. Untuk itu diperlukan deteksi dini untuk mengenali kecenderungan kecanduan pornografi pada anak melalui kegiatan yang menyenangkan dan bermanfaat. Tujuan dalam penelitian ini adalah melihat gambaran kecenderungan kecanduan pornografi pada anak Sekolah Dasar. Metode penelitian menggunakan kuasi eksperimen, yang akan mengukur kecenderungan kecanduan pornografi melalui kegiatan psikodrama dan pelatihan pubertas, dengan alat ukur yang dimodifikasi dari alat ukur Kecanduan internet oleh Young, dengan nilai realibilitas 0,72. Responden berasal dari 3 Sekolah Dasar di Jakarta Barat sebanyak 190 Siswa. Kegiatan pelatihan persiapan pubertas yang dimulai dengan psikodrama baik dilakukan untuk pendeteksian kecanduan pornografi. Mayoritas siswa pernah melihat gambar/adegan pornografi (86,3 %), tidak sengaja 73,2 %, dilihat di rumah sendiri 30,5 %.dan warnet 22,1 %, melalui Hp dan komik 39,5 % % serta games 37,4 %. Perasaan setelah melihat pornografi mayoritas jijik ( 46,4%), biasa-biasa saja 15,8%, terangsang 2,6%. Sikap setelah melihat pornografi mayoritas kapok (62,6%), biasa-biasa saja 15,8 %, dan ketagihan 2,6 %. Tingkat kecenderungan kecanduan pornografi cenderung sedang (69,5% ) rendah 18,9 % dan tinggi 11,6 %. Ada hubungan antara kegiatan siswa dan tingkat kecenderungan kecanduan pornografi dengan asal sekolah. Kata kunci : pornografi, psychodrama, kuasi eksperimen